Enhancement of the optoelectronic characteristics of deep ultraviolet nanowire laser diodes by induction of bulk polarization charge with graded AlN composition in AlxGa1-xN waveguide - Nawaz, Sharif Muhammad; Niass, Mussaab Ibrahim; Wang, Yifu; Xing, Zhongqiu; Wang, Fang; Liu, Yuhuai (Superlattices and microstructures, 2020)
AlGaN based Nanowire laser diodes (NW-LDs) grown on sapphire substrates have strong polarization induced electric field. Such electric field has the ability to degrade the optoelectronic characteristics of deep ultraviolet (DUV) NW-LD. In this work, a graded AlN composition AlxGa1-xN waveguide (WG) layer is used for the enhancement of DUV NW-LD performance. Grading of WG induces bulk polarization charges which compensates the effect of polarization induced electric field. According to the calculated optoelectronic characteristics of NW-LD, it is found that grading of n-type WG (n-WG) increases the optical confinement factor (OCF) by 82%. Fortunately, the proposed graded n-WG structure suppresses the leakage of optical field from active region and enhances carrier injection efficiency. Furthermore, if both n-WG and p-WG graded layers are used, the improvement is not obvious because of the current leakage from graded p-WG. Thus, graded n-WG based NW-LD gives highest 33.5% OCF with the lowest 7 mA and 4.59 V threshold current and voltage respectively. •WG grading induces bulk polarization charge, which suppresses the field leakage from active media.•Grading of n-type WG (n-WG) increases the optical confinement factor (OCF).•As compared to the step graded WG and double graded WG structure, a single only graded n-WG NW-LD structure provides better performance.